Analysis of the Distribution and Sharia Compliance of Bank Muamalat’s Kuningan Branch “Soleh” (Hijrah Gold Solution) Product in the Digital Age - Ela Nurlaela; Siti Aisah; Sri Rahayu; Misbahul Khoer; Sri Rokhlinasari; Alvien Septian Haerisma (JURNAL ECONOMINA, 2026)
This study aims to analyze the distribution mechanism and sharia compliance of the Solusi Emas Hijrah (SOLEH) product at Bank Muamalat in the digital era. The research uses a qualitative descriptive approach with a case study design. Data were collected through in-depth interviews, documentation, and literature studies, and analyzed using data reduction, data display, and conclusion drawing techniques. The results show that the gold financing mechanism through SOLEH is conducted using murabaha and rahn contracts, both manually and digitally through the Muamalat DIN application. From a sharia perspective, the implementation has complied with the principles set by DSN-MUI and international standards, including asset ownership, price transparency, and contract clarity. The use of digital systems in this product also reflects the concept of constructive possession (qabd hukmi). However, continuous supervision is required to minimize potential uncertainty risks. This study contributes to the development of digital Islamic financial services while maintaining sharia compliance.